Do remittances affect labour participation decisions and hours worked? Evidence from Ethiopia - Haile Ademe Ayalew; Pratap C. Mohanty (Cogent Economics & Finance, 2022)
The present study examines the impact of remittances (foreign and domestic) on labour participation decisions and hours worked in Ethiopia. By exploiting nationally representative panel data obtained from the Ethiopian Socio-Economic Survey (ESS) 2013/14 and 2015/16, this study finds that receiving foreign remittances has a negative impact on the adult labour participation decisions and hours worked in Ethiopia. Its effect is also conditional on occupation, gender, and residential location. However, the impact of domestic remittances on the decision to participate in the non-domestic labour activity is mixed by residential location. Labour participation decisions for rural adults has increased but decreased for the urban. Its effect on the labour participation decisions in temporary paid jobs is also positive. On the other hand, this study finds that child labour participation decisions and hours worked are neither affected by the amount of foreign and domestic remittances nor by remittance-receiving status. The econometric technique applied logit and Tobit models, and a robustness check has been carried out using the per adult equivalent amount of remittances. This study suggested that further studies to identify causes for the negative effects on labour participation decisions and hours worked are critical to designing an appropriate policy. However, since it increases adult labour participation in rural areas and participation in temporary paid jobs, enabling policies to increase domestic remittances are highly important.
Keywords: F22; F24; F65; J01; J08; 330; Labour participation; hours worked; foreign remittance; domestic remittance; Ethiopia